Torch agents in neonates and in infants in Turkey - Kanra, Güler; Gürses, Nuran; Seçmeer, Gülten; Ünal, Meral; Günalp, Altan (The Turkish Journal of Pediatrics, 1979)
Three positive results obtained in the course of this study point out the value of the investigation for the Torch agents.